Farmers' Perception on Production Constraints, Trait Preference and Variety Selection of Chickpea (Cicer arietinum L.) in Kenya - Kosgei, Alice; Gaur, Pooran M.; Kimurto, Paul; Yeboah, Martin; Offei, Samuel; Danquah, Eric (Journal of African Interdisciplinary Studies (JAIS), 2021)
Chickpea production is mainly practiced on a small scale with productivity per hectare lower than the world average and a relatively slow adoption rate. This study investigated farmers’ production constraints, preferred traits, and selection criteria for specific varieties. A participatory Rural Appraisal (PRA) through Focus Group Discussions (FGD) was conducted in Bomet and Embu counties. The direct ranking was used to identify farmers’ variety preference. Data collected was analysed using Statistical Package for the Social Sciences (SPSS) software. Farmers indicated that major production constraints were pests and disease, drought, and lack of early-maturing varieties. The preferred varieties were ICCV 97105, ICCV 92944, and ICCV 00108 due to high yielding, drought tolerant, early maturing, and pest and disease resistance. Farmers also had a higher preference for Desi than Kabuli types. From the study, farmers have preferences and breeders should aim at developing varieties with multiple traits for increased production and adoption.
Keywords: Chickpea adoption; Chickpea constraints; Chickpea yield; Drought; Farmer-preference; Participatory Rural Appraisal (PRA)